Geriatric emergency medicine—a model for frailty friendly healthcare. (21st March 2022) - Mooijaart, Simon P; Carpenter, Christopher R; Conroy, Simon P
Abstract: As the world's population continues to age over the decades ahead, medical educators and researchers in every adult medical and surgical specialty will need to 'geriatricise' their clinical science. Many have already engaged with geriatrics. Here we describe the progress that has been made and the opportunities ahead in the field of Geriatric Emergency Medicine (GEM), a field that has taken large steps in integrating holistic care. Future opportunities exist in the three domains of evidence-based medicine: including patient preferences and needs, generating scientific evidence, and improving physician knowledge and expertise. Implementation requires new innovations also in the organisation of care. Similar strategies may be useful in other fields of medicine, in making holistic care the standard for older people.